(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Dengue hemorrhagic fever (DHF) is an acute infectious disease that can become an epidemic caused by the dengue virus. The disease is spread by Aedes mosquitoes that bite infected people and then transmit the disease to healthy people through bites. The two types of Aedes mosquitoes that transmit the disease are scientifically named Aedes aegypti and Aedes albopictus. To answer the question about the current status of DHF vectors, the distribution characteristics, behavior and different habits of Ae. aegypti and Ae. albopictus mosquito populations in some inner-city districts with high risk of DHF in Ho Chi Minh City, there is currently very little data; do the chemical control measures commonly used today when spraying and killing larvae and mosquitoes that transmit DHF lead to a risk of forming resistance to chemicals in the mosquito population? We conducted the project with the aim of: Assessing the composition, distribution, resting habits, chemical resistance and the role of transmitting dengue fever of Aedes spp. mosquitoes in the inner city of Ho Chi Minh City. Research subjects and methods: For Aedes spp. mosquitoes and larvae collected in District 8, Ho Chi Minh City: all mosquitoes and larvae were collected from households (inside and outside the house, around water containers, bushes, etc.) by systematic random sampling based on a sample frame of a list of households managed by local authorities to investigate mosquitoes, monitor adult mosquitoes by catching mosquitoes resting indoors and outdoors with a tube or handheld vacuum cleaner. Catch mosquitoes resting on clothes, blankets, and household objects during the day. Record the resting places of Aedes spp. mosquitoes in household living spaces, each household catches mosquitoes for 15 minutes. Detection of Dengue virus in Ae. aegypti and Ae. albopictus mosquitoes by Multiplex reverse Transcriptase PCR. Results: In this study, with 120 surveyed households, 88 Aedes spp. mosquito samples were collected, including 87 Ae. aegypti samples and 01 Ae. albopictus sample, indoor accounts for 98.9%, mainly Aedes aegypti); outdoor accounts for 1.1%, mainly Aedes albopictus during the survey period. Among the Aedes spp. mosquitoes collected (mainly Aedes aegypti), the resting rate in the living space of households has the following specific rates: bedroom: 34.5% living room: 28.7%, kitchen: 26.5%, toilet: 10.3%. Regarding the resting substrate, Aedes aegypti mainly rests on clothes 62.5%, other substrates (such as fans, shelves, etc.) 19.3%, on walls 15.9%, mosquito nets 2.3%. The resting height of Ae. aegypti in houses is mainly from 1 - ≤ 2 meters: 86.4%; Dengue virus agent has not been detected by SHPT Aedes aegypti technique and Aedes albopictus mosquitoes collected in the field will be determined. Conclusion: Through this study, we recorded some resting habits of Aedes spp in the inner city area of ​​Ho Chi Minh City with high risk of dengue fever mainly in bedrooms, resting on clothes at a height of 1-2 m, Dengue virus has not been detected in collected mosquitoes.